Self-reported asthma prevalence and management in adults in France in 2018: ASTHMAPOP survey - Raherison-Semjen, Chantal; Izadifar, Armine; Russier, Maud; Rolland, Christine; Aubert, Jean-Pierre; Touboul, Chantal; Leynaud, Delphine; Fabry-Vendrand, Caroline; Didier, Alain (Respiratory medicine and research, 2021)
There is a paucity of epidemiological data on asthma classified by disease severity in France. The ASTHMAPOP cross-sectional study aimed to review the prevalence and current management of asthma in people aged ≥18 years in France. A self-administered questionnaire was mailed to 19 676 people representative of the French population in age, gender, region, and socio-economic status. Asthma was classified by treatment steps per the 2017 Global Initiative for Asthma (GINA) report, according to prescribed treatments. Analyses were mostly descriptive. The questionnaire return rate was 81.7% (n = 16 083), and 15 587 questionnaires were analyzed. The prevalence of lifetime asthma was 12.8% (95% confidence interval (CI):12.3−13.3%; n = 1 989) in 2018. The prevalence of current asthma (i.e., 12 months before the survey) was 6.4% (95% CI: 6.0−6.8%; n = 993); most of these respondents (95.3% [n = 946]) were receiving asthma treatment, and 49.4% (n = 491) were treated for mild asthma (GINA step 1 or 2). Of people with current asthma, 47.6% reported ≥1 asthma exacerbation in the past 12 months—defined as episodes (several days) during which symptoms (cough, sputum, and dyspnea) were worse than usual; 14.3% had ≥1 emergency visit, and 3.1% had ≥1 hospitalization due to asthma. Of those taking continuous asthma controller medications who answered all Morisky Medication Adherence Scale questions (n = 501), 46.4% were adherent (score=4) to their treatment regimen. Based on the 6-item Asthma Control Questionnaire scores, asthma was partially controlled or uncontrolled in 47.7% of 969 people. The prevalence of asthma in France has remained stable since 2006, but levels of asthma control and treatment adherence continue to be relatively poor. Asthma management in France requires improvement.